CORRECTION OF PARTIAL DEFECTS OF THE EXTERNAL EAR - Y.P. Nagirnyi (Ukrainian Medical Stomatological Academy, 2016)
In foreign literature plastic surgery provides this classification of traumatic ear defects: a complete loss of the ear, ear partial defects, including conventionally distinguished defects: the top third of the ear, the middle third of the ear, the lower third of the ear. Total loss of the ear is rare, because even in the most severe traumatic injuries of the outer ear some part of it (usually of shells and ear canal) still remains. Reconstruction of defects is difficult, but the tactics are similar and include three main phases: recovery framework that provides external ear shape, restoring the skin of the ear and possible further correction for best results. "Gold standard" method is recognized shelter frame of solid material of rotated temporal fascia flap with axial blood flow; the entire structure is covered with split skin graft. As for the frame, there are many options - a cut in the patterns of intact ears costal cartilage, synthetic material - standard form or individually made and so on, but we are more interested in partial ear defects. Several authors indicate that it's much more appropriate to replantate not all lost segments, but only the cartilaginous part. Cartilaginous skeleton of outer ear is so hard to recreate. There are many methods of replantation of the lost cartilage. For example, you can clear the cartilage covering and place it under the skin of the anterior abdominal wall, neck or mastoid area. Of course, it's not easy to perceive the whole variety of ways of partial reconstruction of the outer ear, although not all of them have been listed. Note the common principle of all methods has been presened (with the exception of free transplant fragments of contralateral ear. We can assume that synthetic implant frame has the advantage over autologous that is not destroyed by ischemia and doesn't impose on skin flap perfusion additional burden with which ischemic tissue can not handle. Ischemia graft is a big problem for ear reconstruction. This is why the method of rotation in the axis of the temporal fascia of superficial temporal vessels is recommended. The method has proven itself as the most reliable and should be considered as a first option when planning any operation on the reconstruction of the outer ear.